Perencanaan Penggantian Komponen CVT pada Sepeda Motor Matik 160 cm3 - Fahmi Faadhilah; Syamsul Hadi; Fitrianoor Anasia Pratama; Fajar Sugiharto; Arief Deny Setiawan; Fadilah Taufiqur Rohman (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Progressive wear on drive belt components, brake lining thickness, double lining bowl and other components of continuously variable transmission (CVT) on 160 cm3 automatic motorcycles are the problems faced. The purpose of component replacement planning is to obtain maintenance costs in 2026 and maintenance to profit ratio. The component replacement planning method includes collecting previous maintenance data, applying the inspection-replace-repair-overhaul (IRRO) method, evaluating component conditions, predicting component lifespan, predicting labor costs, predicting supporting equipment and supporting materials to be used in maintenance, predicting spare part replacement time, predicting maintenance costs in 2026, and calculating the maintenance cost to profit ratio. The results of component replacement planning obtained maintenance costs in 2026 are IDR 8.151.667,- with an estimated rental rate for Automatic Motorcycles of IDR 12,500/hour which has the potential to be rented for 3960 hours/year, and the ratio of maintenance costs to profits is 16.4% which implies that the 160 cm3 Automatic Motorcycle which was first used in 2021 is still prospective to generate profits and is suitable for use in the coming years.